Data integration in the life sciences : 12th International Conference, DILS 2017, Luxembourg, Luxembourg, November 14-15, 2017, Proceedings /: 12th International Conference, DILS 2017, Luxembourg, Luxembourg, November 14-15, 2017, Proceedings. (2017) - Unknown
No abstract available